A Terceira Vitória da Frelimo em Moçambique: Marginalização Política ou Estabilidade Económica? - Pais, Rita (Africana Studia, 2020)
Mozambique’s latest parliamentary and presidential elections, in December 2004, confirmed two aspects that have been visible since the country opened up to a multi-party system. On one hand, the two major parties, Renamo and Frelimo, continue to dominate the political scene, since a third force hasn’t emerged as a real alternative. On the other hand, the weaknesses of Renamo’s political organisation has become more evident, and reflected on the electoral results. Frelimo’s comfortable victory and the declaration, by international observers, of the elections as free and fair (even though some irregularities were identified), strengthened the image of stability that the Frelimo government has been trying hard to build, at the same time that it guaranteed the donor’s renewed vow of confidence on the country’s development programs. The Interpretation of these elections’ results ranges from political marginalization to economic stability.